The impact of dermatology educational programs on school-aged children. Systematic review. - Sa, B.; Burke, O.; Kaiser, R.E.; Sasser, A.; Schmidt, F.B. (European Journal of Pediatric Dermatology, 2026)
Background/Objectives. Dermatologic conditions, particularly those affecting adolescents, can significantly impact mental health, self-esteem, and social development. Acne, eczema, and psoriasis are frequently associated with emotional distress, social isolation, bullying, and an increased risk of suicide. Although early interventions aimed at reducing stigma, educating on skin care, and fostering empathy are critical, time constraints during healthcare visits often limit the delivery of comprehensive education. This systematic review evaluates the effectiveness of dermatology educational programs targeting school-aged children, focusing on their impact on dermatologic knowledge, behavior change, and empathy. Methods. A systematic review was conducted using studies from diverse geographic regions that examined school-based or community dermatology education programs for children. Inclusion criteria focused on interventions reporting outcomes related to dermatologic knowledge, behavioral changes, and psychosocial effects such as empathy or stigma reduction. Results. The reviewed programs demonstrated improvements in dermatologic knowledge, adoption of healthier skin care behaviors, and increased empathy toward individuals with visible skin conditions. Some interventions also reported reductions in bullying and stigmatizing attitudes. However, challenges such as cultural barriers, inconsistent program implementation, and knowledge decay over time were noted. Conclusions. Dermatology educational programs for school-aged children show promise in enhancing dermatologic literacy, promoting empathetic behavior, and reducing stigma associated with skin conditions. To maximize impact, culturally tailored, ongoing initiatives should be integrated into school curricula and community settings. These efforts may contribute to improved dermatologic, psychological, and social outcomes, addressing health disparities among pediatric populations.